The effect of long-term storage on the viability and properties of Alternaria alternata, Bipolaris sorokiniana and Fusarium solani strains of the Phytopathogenic Microorganisms State Collection of ARRIP - N. S. Zhemchuzhina; M. I. Kiseleva; S. A. Elizarova; N. V. Merkuryev (Овощи России, 2024)
Relevance. Under conditions of prolonged storage of fungi on a nutrient agar medium, their pathogenic properties are gradually lost. Preservation of collection material with unchanged pathogenic properties is necessary for correct research, including the development of biological protection methods, monitoring of pathogen development dynamics, assessment of their virulence and aggressiveness, choice of selection material.Materials and Methods. The ability to the resumption of full-fledged species characteristics on the culture nutrient agar medium after long-term storage of the biomaterial in the form of a lyophilizate under conditions of low positive +4°C and ultra-low temperatures of -80°C of Alternaria alternata (Fr.) Keissl., Bipolaris sorokiniana Shoemaker and Fusarium solani (Mart.) Sacc. strains stored in the State Collection of Phytopathogenic Microorganisms of the All-Russian Research Institute of Phytopathology (ARRIP) was studied. The viability of fungi was judged by their ability to form spore-forming colonies on a nutrient medium, pathogenicity and phytotoxicity by the reaction of test culture seedlings to the effects of spore suspensions and culture fluid filtrates.Results. Long-term storage of Alternaria alternata, Bipolaris sorokiniana and Fusarium solani strains in a freeze-dried state, both at low and ultra-low temperatures, did not adversely affect their viability. On the 14th day of culture on a nutrient medium, fungal strains formed sporulating colonies comparable to the control variants. Comparison of pathogenicity signs in fungal strains before the experiment and after storage did not reveal significant differences between the variants. When studying the effect of the culture liquid filtrates of fungal strains on the development of the test culture, a differentiating effect of the storage regime at +4oC was established, while under ultra-low temperatures the results in the variants practically did not differ.Conclusion. The results of the study were showed that the lyophilization of biomaterial,including imperfect species of fungi for long-term storage at low positive and ultra-low temperatures is relevant and in demand in many scientific and industrial institutions.